2008
DOI: 10.1016/j.vetmic.2008.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two novel B cell epitopes on porcine epidemic diarrhea virus spike protein

Abstract: S1D (residues 636-789) is a neutralizing epitope region on the spike protein (S) of porcine epidemic diarrhea virus (PEDV). To accurately identify epitopes on S1D, the S1-phage library containing the gene encoding the S1D region of PEDV S protein was micropanned by six specific monoclonal antibodies (McAbs) against the S1D region. These micropanned epitope regions (MER) were focused on 696-779 amino acids of the S protein. To further map epitopes of the MER, seven overlapping mini-fragments covering MER nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
189
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(192 citation statements)
references
References 20 publications
2
189
0
1
Order By: Relevance
“…There are four major epitope regions in the spike glycoprotein: amino acid positions 504-643 [21], 753 YSNIG VCK 760 [22], 769 LQDGQVKI 776 [22], and 1373 GPRLQPY 1379 [23]. Amino acid position 753 YSNIGVCK 760 (SS2 region) in the S1 domain is conserved between the Vietnam PEDV strains and isolates from other countries.…”
mentioning
confidence: 99%
“…There are four major epitope regions in the spike glycoprotein: amino acid positions 504-643 [21], 753 YSNIG VCK 760 [22], 769 LQDGQVKI 776 [22], and 1373 GPRLQPY 1379 [23]. Amino acid position 753 YSNIGVCK 760 (SS2 region) in the S1 domain is conserved between the Vietnam PEDV strains and isolates from other countries.…”
mentioning
confidence: 99%
“…PEDV has a single-stranded positive-sense RNA genome of approximately 28 kb in size that encodes four structural proteins (spike [S], envelope, membrane [M], and nucleocapsid [N] protein) and four nonstructural proteins (1a, 1b, 3a, and 3b). Among the viral proteins, the S protein that functions in the receptor binding and virus-cell membrane fusion at the time of virus entry represents an important site for virus neutralization [7][8][9][10]. It has been well documented that S proteins of several coronaviruses, such as mouse hepatitis virus (MHV), porcine transmissible gastroenteritis virus (TGEV), avian infectious bronchitis virus (IBV), and human severe acute respiratory syndrome coronavirus, play important roles in virus entry, neutralization, and pathogenicity [11][12][13].…”
mentioning
confidence: 99%
“…Previous studies of the S protein of PEDV have identified neutralizing SS2 (a.a. position 748-755) and SS6 (a.a. position 764-771) epitopes in the S1 domain [10] and 2C10 epitope (a.a. position 1368-1374) in the cytoplasmic Table 1 Primer sequences for amplification of S, M, and N gene and GenBank accession numbers of each passaged 83P-5 strain…”
mentioning
confidence: 99%
“…Similar to other coronaviruses, the S protein of PEDV can be divided into three domains, including a large outer domain, a transmembrane domain and a short cytoplasm domain at the carboxy terminus. It has been demonstrated to have four neutralizing epitopes on the surface of S protein (aa 499-638, 748-755, 764-771, and 1,368-1,374) (Sun et al 2008), which are pivotal in receptor binding and cell entry, host-cell fusion, as well as the induction of neutralizing antibodies (Godet et al 1994, Chang et al 2002, Sun et al 2007). Therefore, the S protein is a suitable candidate for examining the epidemiological status in the field, strain diversity and the association between gene mutations and viral antigenicity of PEDV (Park et al 2007).…”
Section: Primer Namesmentioning
confidence: 99%